Study of an Electric Drive System Powered by Renewable Sources - Kamel KHIARI; Haroune BAIT; ENCA/ Toufik ROUBACHE (University of M’sila, 2025)
This study explores the design, modeling, and control of an electric drive system powered by various renewable energy sources for use in electric vehicles (EVs). The system integrates photovoltaic (PV) systems, fuel cells, batteries, and supercapacitors to create a hybrid energy solution that enhances efficiency, reliability, and sustainability. The study begins with an introduction to renewable energy technologies, including solar, hydrogen fuel cells, and wind power, and examines how these technologies are integrated into EVs drive systems. Additionally, a detailed mathematical model for each component is developed to analyze the behavior and interactions among the energy sources within the system. The conventional Perturb and Observe (P&O) algorithm is employed to track the maximum power point (MPPT) from the photovoltaic (PV) system to the drive system, while optimizing the rotor speed of the drive motor to ensure maximum power transfer to the vehicle. To achieve this objective, a Direct Torque Control (DTC) strategy is utilized for motor speed control. This control approach facilitates maximum energy harvesting and enables the motor to operate with high efficiency under varying load conditions. The simulation results confirm the effectiveness of the implemented scheme, demonstrating stable performance, enhanced energy management, and a reduction in dependence on fossil fuels.
Keywords: Electric drive; Renewable energy source; MPPT; Direct torque control; Double stator asynchronous machine.